Error-augmentation gait training to improve gait symmetry in patients with non-traumatic lower limb amputation: A proof-of-concept study. (August 2019) - Kline, Paul W; Murray, Amanda M; Miller, Matthew J; Fields, Thomas; Christiansen, Cory L
Background: Asymmetrical stepping patterns are chronic gait impairment for individuals with non-traumatic lower limb amputation. Persistent gait asymmetries contribute to poor gait efficiency, decreased physical function, and development of secondary orthopedic conditions. Objectives: Evaluate the feasibility and preliminary responsiveness of a treadmill-based, error-augmentation gait training protocol to improve gait symmetry in patients with non-traumatic transtibial amputation. Study design: Single group, pre- and post-test. Methods: The error-augmentation gait training protocol involved walking on a split-belt treadmill with asymmetrical belt speeds for five 3-min sets. Spatiotemporal gait characteristics during overground walking at self-selected and fast walking speeds were assessed prior to, immediately after, and 20 min following the error-augmentation gait training protocol. Outcomes included practicality, implementation feasibility, safety, participant acceptability, and change in gait asymmetry. Results: All four participants completed the error-augmentation gait training protocol as prescribed, without adverse events, and found the intervention to be acceptable. Step length and stance time asymmetry during overground walking changed immediately following the error-augmentation gait training protocol with inconsistent changes retained after a 20 min washout period. Conclusions: A single session of error-augmentation gait training is a feasible and safe intervention to modify gait asymmetry in patients with non-traumatic transtibial amputation. Additional study with larger sample sizes and repeated error-augmentation gait training dosing are warranted. Clinical relevance: Gait training using error-augmentation on a split-belt treadmill may modify step length and stance time asymmetry for patients with non-traumatic transtibial amputation, but additional research is needed regarding short- and long-term efficacy. Additional training sessions may be needed to sustain initial changes achieved from a single session.